Vertical Relationships and Competition in Retail Gasoline Markets: Empirical Evidence from Contract Changes in Southern California - Hastings, Justine S (American Economic Review, 2004)
Vertical Relationships and Competition in Retail Gasoline Markets: Empirical Evidence from Contract Changes in Southern California by Justine S. Hastings. Published in volume 94, issue 1, pages 317-328 of American Economic Review, March 2004